Calidad del servicio y satisfacción del usuario en relación con el servicio de agua potable y saneamiento en Iquitos - Perú - Santa Cruz Arévalo, Johanna Elena (2025)
The research conducted in Iquitos employed a non-experimental design, with 384 surveys administered to a representative sample. The findings indicate that users report feelings of insecurity and dissatisfaction regarding various factors, including: investment projects, communication about cleaning plans, responses to claims for damages, and the challenges faced by the water supply network in ensuring household access to potable water. Consequently, overall user satisfaction was rated at a moderate level. A correlation coefficient of 0.790 with a significance level of 0.000 indicates a statistically significant relationship between the study variables. In conclusion, the water provided for daily consumption rarely meets the established chemical, physical, and microbiological standards; thus, the quality of the sanitation service in Iquitos is considered limited.